Insecticidal Effectiveness Test of Mahogany Fruit Peel (Swietenia Mahagoni (L.)) Extract on Mosquito Aedes Aegypti for Increasing Economy - Erisa Mutiara Rahma Delvina; Selvi Marcellia; Tutik Tutik (Budapest International Research and Critics Institute (BIRCI-Journal): Humanities and Social Sciences, 2021)
Mahogany rind which is underutilized in the environment contains secondary metabolites that have the potential as insecticides such as alkaloids, flavonoids, tannins, and saponins. The purpose of this study was to determine the mahogany rind extract was effective as an insecticide in controlling the mosquito vector Aedes aegypti and to determine the concentration of the mahogany rind extract which was most effective as an insecticide for the Aedes aegypti mosquito. Mahogany rind extraction method with percolation method using ethanol as solvent. The extraction result of mahogany rind was 21 grams with a yield of 5.428%. Mahogany rind extract has effectiveness as an insecticide against Aedes aegypti mosquitoes. The results showed that the higher the concentration of mahogany skin extract, the more the number of Aedes aegypti mosquitoes dead. The lowest killing power to the one that effectively kills mosquitoes is 0.5%, 1%, 2%, and 4% with a mortality of 14.28%, respectively; 21.42%; 45.53% and 57.14%. In the probit analysis LC50 of mahogany fruit peel extract is at a concentration 3.796% and including the poisonous category.